G337(P) Low cost red LED bicycle lights for transillumination of veins in neonates: A comparison with traditional cold lights. (27th April 2016) - Russell, N; Chang, J
Abstract : Difficult intravenous access can compromise patient care in Neonatal and Paediatric practice, and transillumination is often used to facilitate cannulation. However devices for transillumination are prone to bacterial contamination, potentially contributing to cross infection, as well as being expensive and unaffordable in low-resource settings. Unlike many cold lights, red LED bicycle lights are cheap (<£1), portable, and small enough to be enclosed fully inside a glove, reducing the potential for cross infection when used at the cot-side. After demonstrating their safety and lack of temperature rise on formal testing, and subsequently gaining ethical approval for a pilot randomised controlled trial which is ongoing, we conducted this proof of concept study comparing the quality of transillumination using 'cold lights' with low-cost LED bicycle lights in clinical photographs. 30 photographs of the hands and feet of neonates were taken with written parental consent, firstly without transillumination (10 controls), and then with bicycle lights (10) and cold lights (10). Photographs were sent via an online survey to paediatric doctors who were binded to the intention of the study and to the method of transillumination. Respondents were asked to rate the visibility of the veins in each picture, on a scale of 1=Invisible, 2=Barely visible, 3=Moderately visible, 4=Easily visible. 125 questionnaires were returned, in which 94.7% of respondents rated the veins Moderately or Easily visible in the bicycle light group, vs 87.7% in the cold light group, and 43.1% in the control group. This study shows that low-cost bicycle lights provide a quality of transillumination which is comparable with cold lights. Given their many other advantages such as cost, ease of use, portability, and potentially reduced risk of cross infection, they could be considered for use in routine practice for venous transillumination, particularly in low-resource settings where other methods of transillumination are unaffordable.